I2-Catalyzed transformation of o-aminobenzamide to o-ureidobenzonitrile using isothiocyanates. Issue 14 (23rd March 2020) - Shamanth, Sadashivamurthy; Chaithra, Nagaraju; Gurukiran, Mahesha; Mamatha, Mahesha; Lokanath, N. K.; Rangappa, Kanchugarakoppal S.; Mantelingu, Kempegowda
Abstract : The present work describes an unexpected and unique protocol for the iodine catalysed synthesis of o -ureidobenzonitriles using o -aminobenzamides and isothiocyanates via intramolecular rearrangement. Abstract : The present work describes an unexpected and unique protocol for the iodine catalysed synthesis of o -ureidobenzonitriles using o -aminobenzamides and isothiocyanates via intramolecular rearrangement. The metal-free route achieved here is insensitive to moisture and applicable to the synthesis of a wide variety of o -ureidobenzonitriles with excellent yields even in a scalable fashion.